TRANSFRONTIER CONSERVATION, LIVELIHOODS AND SUSTAINABLE TOURISM- A REVIEW OF COMMUNITY PERCEPTIONS OF THE VALUE OF THE GREAT LIMPOPO TRANSFRONTIER CONSERVATION AREA (GLTFCA) - Chiutsi, Simon (European Scientific Journal, ESJ, 2014)
The study examines community perceptions about the utility of the Great Limpopo transfrontier tourist destination in developing livelihoods and facilitating community participation in the tourism industry. The study indicates that the level of community satisfaction with the Transfrontier initiativeis at its lowest since its inception. The community perception of the economic value of the GLTFCA to both household and community level was rated lowly. The findings confirm that as households become more satisfied with the performance of GLTFCA they are more likely to participate in tourism related activities. It is also observed that an increase in perceived GLTFCA economic value to households increases the participation of the community in sustainable conservation and tourism. What it all adds up to is that to improve the overall rating of the GLTFCA by the community there is need to increase community participation in tourism enterprise through partnerships with both the private and public sector. There is need for the GLTFCA management to engage in activities that improve livelihoods sustainability as these will increase the perceived economic value of GLTFCA at household level.